THE RESONANT OVERVOLTAGE IN NON-SINUSOIDAL MODE OF MAIN ELECTRIC NETWORK - V. G. Kuznetsov (Електротехніка і електромеханіка, 2018)
Purpose. The resonant overvoltage arises in main electrical networks as a result of random coincidence of some parameters of circuit and its mode and it may exist for a relatively long time. Therefore, the traditional means of limitation of short duration commutation surges are not effective in this case. The study determines conditions of appearance and development of non-sinusoidal mode after switching idle autotransformer to the overhead line of extra high voltage. The purpose of the paper is to choice measures for prevention overvoltage, too. Methodology. The study has used the result of extra high voltage line testing, the methods of electric circuit theory and the simulation in the MATLAB & Simulink package. Results. The simulation model of the extra high voltage transmission line for the study of resonant non-sinusoidal overvoltage is developed. The conditions for the appearance of resonant circuits in the real power line are found and harmonic frequency in which overvoltage arises are obtained. The study proposes using the controlled switching device as a measure to prevent resonance surges and determines the appropriate settings. Originality. The expression for calculation of resonant length of extra high voltage line was derived. The special investigation of processes in the resonant circuit of the extra high voltage transmission line for higher harmonic components of voltage is carried out. The program of switching for control apparatus that prevents non-sinusoidal overvoltage has been developed at the first time. Practical value. The using of the proposed settings of controlled switchgear will prevent the occurrence of hazardous resonant surge on higher harmonic components of voltage.